1981
DOI: 10.1515/cclm.1981.19.9.953
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Inhibition Studies of Bacillus cereus β-Lactamase Using a Spectrophotometric Method

Abstract: The use of a Spectrophotometric method is reported for the characterization of a /Mactamase (EC 3.5.2.6) from Bacillus cereus. Absorption coefficients of the mercaptids of various penicillins were determined with this method. The enzyme was kinetically characterized using penicillins.Inhibition studies with Bacillus cereus 0-lactamase and various penicillins showed a substrate type of inhibition, indicating an additional binding site for substrates without catalytic activity.The dissociation constant of this b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Also, we obtained Hills coefficients (n = 2.1 ± 0.2 and x = 4.9 ± 0.7 for carbenicillin and n = 1.1 ± 0.2 and x = 3.6 ± 0.7 for oxacillin) which indicated cooperative effects in both the hydrolysis and inhibition by carbenicillin, while only inhibition by oxacillin demonstrated cooperative manner. To the best of our knowledge, substrate inhibition is not unique among β-lactamases, however it seems that it is the first example among non-metallo-β-lactamases [ 32 , 33 ]. Currently, the exact mechanism of substrate inhibition for β-lactamases is unknown but it was suggested that it might be linked to the bulky aromatic ring substitutions in some of the antibiotics and the peculiarities of the active sites of β-lactamases [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, we obtained Hills coefficients (n = 2.1 ± 0.2 and x = 4.9 ± 0.7 for carbenicillin and n = 1.1 ± 0.2 and x = 3.6 ± 0.7 for oxacillin) which indicated cooperative effects in both the hydrolysis and inhibition by carbenicillin, while only inhibition by oxacillin demonstrated cooperative manner. To the best of our knowledge, substrate inhibition is not unique among β-lactamases, however it seems that it is the first example among non-metallo-β-lactamases [ 32 , 33 ]. Currently, the exact mechanism of substrate inhibition for β-lactamases is unknown but it was suggested that it might be linked to the bulky aromatic ring substitutions in some of the antibiotics and the peculiarities of the active sites of β-lactamases [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…β‐LEAP is designed in such a way that, upon cleavage by β‐lactamase (Scheme ), the PS is released from homodimeric, ground‐state quenching to yield an enzyme‐specific, light‐activated antimicrobial action. The β‐lactamases were ideal targets for this proof‐of‐principle study owing to the prevalence of β‐lactamase expression among bacteria and its high enzymatic efficiency 8. 9…”
Section: Methodsmentioning
confidence: 99%